A spectroscopic study of the merging dwarf galaxy PGC 007782 - Shankar Timalsina; Daya Nidhi Chhatkuli (Bibechana)
We did a detailed spectroscopic study of PGC 007782, an interacting emission type dwarf galaxy. This study utilized the optical spectrum of emission lines to explore the system of interacting dwarf galaxies. Gaussian fitting techniques were used to examine the main spectral lines such as Hα, Hβ, Hγ, SII, OIII, and NII in order to find out Gaussian parameters. Our investigation focused on the prominent emission lines with wavelengths ranging from 4342 Å to 6733 Å, among them, Hα is the most prominent line having flux of 72.16 × 10⁻¹⁷ erg/s/cm²/Å corresponds to the central wavelength of 6564 Å. With the flux of 2.93 × 10⁻¹⁷ erg/s/cm²/Å, the NII line is the weakest at the central wavelength of 6550 Å. The SII line has the highest FWHM value of 4.04 Å, indicating a higher gas temperature. Each of these emission lines exhibits a nearly perfect Gaussian profile, with a regression coefficient exceeding 91%. Utilizing the Hα line, the star formation rate of PGC 007782 after extinction correction is calculated to be 0.0136 M⊙​yr-1, indicating the galaxy's core is where active star formation is concentrated. The calculated value of Balmer decrement is 4.02 which is higher than the normal value indicating the light coming out from this galaxy is being blocked by the dust particles. With oxygen abundance of 8.31dex, the physical and morphological characteristics of PGC 007782 confirmed this galaxy as a metal poor, actively star forming blue compact dwarf (BCD) galaxy.